Respuesta :

Answer:

[tex]\displaystyle s = \frac{2ab\cos x}{a+b}[/tex]

Step-by-step explanation:

We want to find a formula for s in terms of a, b, and cos(x).

Let the point where s intersects AB be D.

Notice that s bisects ∠C. Then by the Angle Bisector Theorem:

[tex]\displaystyle \frac{a}{BD} = \frac{b}{AD}[/tex]

We can find BD using the Law of Cosines:

[tex]\displaystyle BD^2 = a^2 + s^2 - 2as \cos x[/tex]

Likewise:

[tex]\displaystyle AD^2 = b^2+ s^2 - 2bs \cos x[/tex]

From the first equation, cross-multiply:

[tex]bBD = a AD[/tex]

And square both sides:

[tex]b^2 BD^2 =a^2 AD^2[/tex]

Substitute:

[tex]\displaystyle b^2 \left(a^2 + s^2 - 2as \cos x\right) = a^2 \left(b^2 + s^2 - 2bs \cos x\right)[/tex]

Distribute:

[tex]a^2b^2 + b^2s^2 - 2ab^2 s\cos x = a^2b^2 + a^2s^2 - 2a^2 bs\cos x[/tex]

Simplify:

[tex]b^2 s^2 - 2ab^2 s \cos x = a^2 s^2 - 2a^2 b s \cos x[/tex]

Divide both sides by s (s ≠ 0):

[tex]b^2 s -2ab^2 \cos x = a^2 s - 2a^2 b \cos x[/tex]

Isolate s:

[tex]b^2 s - a^2s = -2a^2 b \cos x + 2ab^2 \cos x[/tex]

Factor:

[tex]\displaystyle s (b^2 - a^2) = 2ab^2 \cos x - 2a^2 b \cos x[/tex]

Therefore:

[tex]\displaystyle s = \frac{2ab^2 \cos x - 2a^2 b \cos x}{b^2- a^2}[/tex]

Factor:

[tex]\displaystyle s = \frac{2ab\cos x(b - a)}{(b-a)(b+a)}[/tex]

Simplify. Therefore:

[tex]\displaystyle s = \frac{2ab\cos x}{a+b}[/tex]

ACCESS MORE
EDU ACCESS
Universidad de Mexico